2023
DOI: 10.1093/nar/gkad521
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved transcriptomic analysis of the germinating barley grain

Abstract: Seeds are a vital source of calories for humans and a unique stage in the life cycle of flowering plants. During seed germination, the embryo undergoes major developmental transitions to become a seedling. Studying gene expression in individual seed cell types has been challenging due to the lack of spatial information or low throughput of existing methods. To overcome these limitations, a spatial transcriptomics workflow was developed for germinating barley grain. This approach enabled high-throughput analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 130 publications
2
6
0
Order By: Relevance
“…We found TIP1;1 abundance to be greater in Flinders than in IGB1467. TIP1;1 is known to be a housekeeping APQ involved in the establishment of basal tonoplast hydraulic conductance. , Therefore, TIP1;1 abundance may contribute to the initially increased water uptake seen in Flinders, although we saw a greater increase in the level of TIP1;1 in IGB1467 from 0 to 24 HAI (Figure D) suggesting an additonal role discussed further below. These findings are also supported by our discovery and quantitative proteomics results presented in our previous study, where TIP1;1, TIP3;1, and TIP3;2 are in the raw grain of IGB1467 and Flinders, with greater abundance in Flinders.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found TIP1;1 abundance to be greater in Flinders than in IGB1467. TIP1;1 is known to be a housekeeping APQ involved in the establishment of basal tonoplast hydraulic conductance. , Therefore, TIP1;1 abundance may contribute to the initially increased water uptake seen in Flinders, although we saw a greater increase in the level of TIP1;1 in IGB1467 from 0 to 24 HAI (Figure D) suggesting an additonal role discussed further below. These findings are also supported by our discovery and quantitative proteomics results presented in our previous study, where TIP1;1, TIP3;1, and TIP3;2 are in the raw grain of IGB1467 and Flinders, with greater abundance in Flinders.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have found that the protein storage vacuole-specific TIP1;1, TIP3;1, and TIP3;2 isoforms are coexpressed and colocalized to the same tonoplast in the germinating grain after imbibition . However, TIP3;1 and TIP3;2 are the only embryo- and endosperm-specific TIP isoforms found in Arabidopsis in the late stages of seed maturation and early-stage germination (phases I and II). During the early-stage of barley germination, Peirats-Llobet et al (2023) found the TIP1;1 isoform was the most abundantly expressed member of the TIP family . We found TIP1;1 abundance to be greater in Flinders than in IGB1467.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows for the examination of how a gene's expression level changes temporally along a continuous process [7][8][9][10][11][12][13] . ST, on the other hand, measures both the gene expression and spatial locations of single cells or small clusters of cells, enabling the direct interrogation of spatial gene expression patterns from the observed data [14][15][16][17][18][19] .…”
Section: Mainmentioning
confidence: 99%
“…Recently, a spatial transcriptomic profiling of germinating barley (Hordeum vulgare) seeds was exhaustively studied by Peirats-Llobet et al [74]. Such methodology (Visium Gene Expression slides, 10x Genomics) allowed for a complete study of gene expression profiles across individual cell types within the plant seeds.…”
Section: Seed Transcriptomesmentioning
confidence: 99%